PENGARUH RASIO LEVERAGE, CORPORATE GOVERNANCE, PERSISTENSI LABA TERHADAP SUKUK RATING DAN IMPLIKASINYA PADA RISIKO DEFAULT - Dini Lestari; Citra Sukmadilaga; Indri Yuliafitri (Journal of Islamic Economy and Business (JIsEB), 2020)
Introduction: This research aims to analyse the impact of leverage ratio, corporate governance, and earning persistence toward sukuk rating and implication to the default risk. Background Problems: The Islamic capital market has developed so that it has a considerable influence on the growth of an Islamic-based economic system in Indonesia. One of the securities traded in this market is sukuk. One of the factors that support the development of sukuk and bonds is the existence of a credible rating. Sukuk rating is very helpful for investors who want to invest in sukuk, so that investors will know the return obtained along with the risks borne. Research Methods: The method used in this research is quantitative descriptive method. The population in this study are all companies that issue outstanding sukuk which are rated by PT. PEFINDO and published annual reports from 2011 to 2017, as many as 12 companies. And 12 companies have outstanding sukuk 21 sukuk multiplied by 7 (seven) years so 147 are observed. Data analysis techniques are path analysis to answer problems related to the impact of leverage ratio, corporate governance, and earning persistence toward sukuk rating and implication to the default risk. Results: Based on the result of statistical test, it concludes that earning persistence and corporate governance is significant positively related to sukuk rating. While rasio leverage is significant negatively related to sukuk rating. Furthermore, sukuk rating is significant negatively related to default risk.. Conclusion: Sukuk rating is influenced by earnings persistence, corporate governance, leverage ratio and sukuk rating.